ICULTOURE.ID Sebagai Media Pendukung Pembelajaran Bahasa Indonesia Terintegrasi Pengenalan Budaya - Purwono, Prahoro Yudo (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2024)
This research aims to develop a virtual learning platform that integrates Indonesian language learning with the introduction of Indonesian culture called "ICULTOURE.ID." The research method used is the ADDIE model development (Analysis, Design, Development, Implementation, Evaluation). The research results indicate that from the needs analysis, it was revealed that there is a significant demand from teachers and students for more innovative and engaging learning methods. Additionally, curriculum studies show the existence of competencies and indicators that support the integration of the Indonesian language with cultural introduction. Parties involved in the development and implementation include teachers, students, technology developers, curriculum experts, and research teams. Teachers need to be involved in introducing and managing the use of this platform in the classroom, while students need to be engaged in providing feedback on design and content. Technology developers are responsible for developing technical infrastructure and platform features that support interactive learning. Curriculum experts offer valuable insights in developing learning materials that align with applicable curriculum standards. The research team plays a role in monitoring and evaluating the implementation of this platform. It is hoped that the development of "ICULTOURE.ID" can provide innovative solutions to enhance Indonesian language learning and cultural introduction in high schools and contribute to efforts to revitalize Indonesian culture among the younger generation.